2022
DOI: 10.1021/acs.chemrev.2c00005
|View full text |Cite
|
Sign up to set email alerts
|

Implants with Sensing Capabilities

Abstract: Because of the aging human population and increased numbers of surgical procedures being performed, there is a growing number of biomedical devices being implanted each year. Although the benefits of implants are significant, there are risks to having foreign materials in the body that may lead to complications that may remain undetectable until a time at which the damage done becomes irreversible. To address this challenge, advances in implantable sensors may enable early detection of even minor changes in th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
26
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 55 publications
(38 citation statements)
references
References 462 publications
(726 reference statements)
0
26
0
Order By: Relevance
“…Thus, any potential monitoring paradigms must be robust during both mechanical failure, device movement and degradation, which represent common failure mechanisms of biomedical devices in diverse areas from hernia patches to knee replacement. [1,30,31] With the promising results on phantom radiopacity at initial time points, we further demonstrated that the incorporation of TaO x nanoparticles resulted in radiopaque phantoms that could be imaged through a 20 week time course, Figure 2. Importantly, the TaO x appeared to remain associated with the polymer matrix, despite loss of structural integrity of the phantoms, allowing for real time characterization of the phantoms which could corroborate the data on mechanical properties and mass loss.…”
Section: Resultsmentioning
confidence: 75%
See 1 more Smart Citation
“…Thus, any potential monitoring paradigms must be robust during both mechanical failure, device movement and degradation, which represent common failure mechanisms of biomedical devices in diverse areas from hernia patches to knee replacement. [1,30,31] With the promising results on phantom radiopacity at initial time points, we further demonstrated that the incorporation of TaO x nanoparticles resulted in radiopaque phantoms that could be imaged through a 20 week time course, Figure 2. Importantly, the TaO x appeared to remain associated with the polymer matrix, despite loss of structural integrity of the phantoms, allowing for real time characterization of the phantoms which could corroborate the data on mechanical properties and mass loss.…”
Section: Resultsmentioning
confidence: 75%
“…Despite their ubiquitous use in the clinic, implants made from polymers fail for a number of reasons, such as wear, tearing, migration and infection. [1] With the inherent risk of failure following implantation of biomedical devices and to prevent situations that could irreparably impact patient health, there exists an increased need for a clinical methodology for in situ monitoring of device status following implantation. [1] However, for the majority of polymer implants, there is no robust endogenous contrast mechanism for clinical diagnostic imaging, and hence no mechanism for radiologists to diagnose problems prior to catastrophic failure.…”
Section: Introductionmentioning
confidence: 99%
“…Next-generation intelligent healthcare sensing is a sophisticated system that monitors patients' physiological signs in real-time, evaluates their health conditions, and details the feedback data to doctors, making medical diagnosis and therapy more predictive and personalized. [1][2][3] Why is this system so comfortable and necessary for biomedical use? The first answer relies on its portable and easy-to-use profiles.…”
Section: Introductionmentioning
confidence: 99%
“…Wearable bioelectronics have increased in popularity over the last decade with the rapid advancement of the Internet of Things and 5G wireless networks. [1][2][3][4] Rather than monitoring intermittently and diagnosing patients in a hospital setting, wearable bioelectronics open the path to continuous healthcare monitoring, [5][6][7][8][9][10][11][12][13][14][15][16] which can contribute to illness prevention through early diagnostics. [17,18] It can also provide a wealth of physiological data for analysis across all sorts of conditions air-permeable textile is capable of reliably providing an output power of 7.975 W m −2 .…”
Section: Introductionmentioning
confidence: 99%